Comparison of the ipsi‐lateral versus contra‐lateral retrograde approach of percutaneous coronary interventions in chronic total occlusions. Issue 4 (5th July 2016) - Mashayekhi, Kambis; Behnes, Michael; Valuckiene, Zivile; Bryniarski, Leszek; Akin, Ibrahim; Neuser, Hans; Neumann, Franz‐Josef; Reifart, Nicolaus
Abstract : Background: Retrograde recanalization of coronary chronic total occlusions (CTO) via contralateral (CL) collateral connections (CCs) is successful in 60–70% of patients in whom conventional antegrade approach fails or is unpromising. This study describes our experience with retrograde CTO‐PCI via ipsi‐lateral (IL) CCs in patients with unfavorable CL CCs. Methods: Between January 2013 and September 2015, 392 consecutive CTO procedures were performed by two high volume CTO‐operators and the relevant data were fed into an online registry (ERCTO® EuroCTO‐club). Most patients (222/392; 57%) were approached antegradely, whereas 43% were attempted retrogradely (170/392). After exclusion of all procedures performed via bypass‐grafts ( n  = 12), PCI via CL CCs, the CL‐group ( n  = 114/158; 72%), was compared with the IL‐group that was attempted via IL CCs ( n  = 44/158; 28%). Results: Both groups were similar with respect to risk factors and morphologic criteria of CTO‐severity. The initial primary strategy was successful in 78% in the CL‐group and in 68% in the IL‐group. In both patient groups, the initial strategy had to be switched in five patients from CL toward IL (4.4%, n  = 5/114) and from IL to CL (11.3% n  = 5/44). The rate of major complications was 7% (CL) and 5% (IL), respectively (n.s.). After retrograde failure and cross‐over to an antegrade controlled re‐entry strategy the overall success rates increased to 92% (CL) and 93% (IL). Conclusions: In experienced hands retrograde CTO‐PCI via IL CCs appears as safe and successful as the CL approach. © 2016 Wiley Periodicals, Inc.